Business Valuation A Case of AVG - Moravec, Marek; Hnilica, Jiří, 1976-; Brabec, Martin; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2013)
The aim of the Master's thesis is to assess the value of AVG to February 1st 2013. The searched value is the value for a potential investor. In order to estimate the value of AVG, the thesis applies two models -- intrinsic and relative. Explicitly, the thesis uses the two discounted cash flow approaches -- the weighted average Cost of Capital method (WACC) and the Adjusted Present Value method (APV). For the purpose of the relative valuation the multiples method is exercised. Finally, the gist of the thesis is the study of risks and benefits of the applied valuation methods in regard to the young high growth company in the Internet industry.
Vedoucí práce: Jiří Hnilica
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses